Differentiation of marrow stromal cells into photoreceptors in the rat eye - Kicic, Anthony; Shen, W.Y.; Wilson, A.S.; Constable, I.J.; Robertson, T.; Rakoczy, P.E. (SOC NEUROSCIENCE, 2003)
Retinal degenerations and dystrophies are the major causes of genetically inherited blindness that are characterized by the apoptotic death of the photoreceptor cell layer of the retina. To date, no treatment exists for these diseases and only recently have they been considered as candidates for gene and stem cell therapies. Here we report the ability of adult CD90+ marrow stromal cells (MSCs) to be induced by activin A, taurine, and EGF into cells (20-32%) expressing photoreceptor-specific markers rhodopsin, opsin, and recoverin in vitro. CD90+ cells were either transduced with recombinant adeno-associated virus expressing green fluorescent protein (GFP) or bromodeoxyuridine (BrdU) labeled and then injected into the subretinal space of adult Royal College of Surgeons rats. Fundus photography and angiography showed no adverse effects of CD90+ MSC transplantation. GFP-expressing cells or BrdU-positive cells covered ∼30% of the entire retinal area. By 2 weeks after injection, CD90+ MSCs integrated into the host retina, forming structures similar to the photoreceptor layer and expressed a photoreceptor-specific marker. No teratoma formation was observed in the recipient retina. The subretinally delivered CD90+ MSCs did not stain for proliferating cell nuclear antigen, indicating that they primarily undergo differentiation rather than proliferation. In addition, we established that transplanted cells can attract synaptic vesicles and hence are potentially capable of signal transduction. This study demonstrates for the first time the partial differentiation of adult CD90+ MSCs into photoreceptors in vitro and in vivo. Our results establish a proof of concept for CD90+ MSC differentiation with autologous transplantation, which may provide a promising therapeutic strategy for the treatment of some forms of genetically inherited retinal degenerations.